"You can't be an atheist here": Christianity and Outward Bound in Britain, c.1941–1965. Issue 1 (1st June 2020) - Freeman, Mark
Abstract : Purpose: The purpose of this study is to explore the role of formal religion in the early years of Outward Bound, a significant outdoor education organisation in Britain, from the 1940s to the 1960s. Design/methodology/approach: This article is based on archival and other documentary research in various archives and libraries, mostly in the United Kingdom. Findings: The article shows that religious "instruction" was a central feature of the outdoor education that Outward Bound provided. The nature and extent of this aspect of the training was a matter of considerable debate within the Outward Bound Trust and was influenced by older traditions of muscular Christianity as well as the specific context of the early post–Second World War period. However, the religious influences at the schools were marginalised by the 1960s; although formal Christian observances did not disappear, the emphasis shifted to the promotion of a vaguer spirituality associated with the idea that "the mountains speak for themselves". Originality/value: The article establishes the importance of organised Christianity and formal religious observances in the early years of Outward Bound, a feature which has generally been overlooked in the historical literature. It contributes to wider analyses of outdoor education, religious education and secularisation in the mid-twentieth century.